Variability and black hole mass in active galactic nuclei - Skelton, Jessica (The University of Edinburgh, 2005)
This thesis explores the links between variability both in X -rays and optical continuum flux and the mass of the central black hole in active galactic nuclei (AGN). The relationships between black hole mass, the mass of the host galaxy spheroid and the emission -line velocity widths are also investigated.

Optical observations of a sample of narrow -line and classical broad-line Seyfert 1 galaxies are presented. Off -nuclear spectra of the bulge were used to obtain the line-of -sight stellar velocity dispersion (δ*). Nuclear spectra were used to remove residual nuclear emission from the bulge spectra and to calculate single -epoch virial black hole mass estimates. The two samples were augmented using objects taken from the literature.

The width of the [O III] 5007å line was found to be a poor estimator of δ* for NLS1s. The ratio δ(FWHM) /δ* was strongly correlated with δ*, suggesting that the NLR only traces the bulge potential well for galaxies with very massive bulges. It was not clear that δ(FWHM) provided a better estimate of δ* for higher-luminosity objects. Only a poor correlation with Eddington ratio was found; however, uncertainties in the estimation of the Eddington ratio make it difficult to assess the significance of this result.

A comparison of δ* for both NLS1s and BLS1s was made. The two distributions were not consistent with being drawn from the same parent population, leading to the conclusion that narrow permitted lines in NLS1s are not due solely to orientation effects. NLS1s were found to be consistent with the relationship between M(BH) and δ* established for inactive galaxies and broad-line AGN. No evidence that soft X-ray selected NLS1s lie preferentially off this relationship was found, although the available sample was small.

The optical flux variability of the least-luminous known Seyfert 1 galaxy, NGC 4395, has been a matter of controversy, with a number of apparently contradictory reports. Optical spectroscopic observations of NGC 4395 are presented, during which the nucleus was monitored every half -hour over the course of three nights. The continuum emission varied by ~35 per cent over the course of three nights, and marginal evidence for greater variability in the blue continuum than the red was found. A number of diagnostic checks were performed on the data in order to constrain any systematic or aperture effects. No correlations were found that adequately explained the observed variability, leading to the conclusion that real intrinsic variability of the nuclear source has been observed. No simultaneous variability was measured in the broad Hß line, although given the difficulty in deblending the broad and narrow components it is difficult to comment on the significance of this result.

The observed short time-scale continuum variability is consistent with NGC 4395 having an intermediate-mass (~10⁵M⨀) central supermassive black hole, rather than a very low accretion rate. Comparison with the Seyfert 1 galaxy NGC 5548 shows that the observed variability seems to scale with black hole mass in roughly the manner expected in accretion models. However the absolute timescale of variability differs by several orders of magnitude from that expected in simple accretion disc models in both cases.

An investigation was made of the relationship between hard (2-10 keV) X-ray variability and both X-ray luminosity (Lₓ) and M(BH•). For objects with secure mass estimates, it was not possible to determine which of these was the primary correlation. However, when high and low accretion-rate objects were included the correlation with Lₓ was found to be very poor, while the M(BH) correlation was still good.